Danggui Buxue Decoction Alleviates Inflammation and Oxidative Stress in Mice with Escherichia coli-Induced Mastitis - Jiamian Wang; Chen Cheng; Yujin Gao; Yina Li; Xijun Zhang; Dan Yao; Yong Zhang (Veterinary Sciences)
(1) Background: Bovine mastitis is a lactational disease caused by infection and milk stagnation in the mammary glands. Danggui buxue decoction (DBD), a traditional remedy for blood tonification, anti-inflammation, and antioxidation, has not been used previously to treat mastitis. (2) Methods: In this study, an Escherichia coli mastitis model was established by infecting lactating Kunming mice with clinically isolated bovine mastitis-derived E. coli. Based on this, the effects of DBD on inflammation and oxidative stress in mastitis model mice were evaluated by conducting routine blood tests, H&E staining, qRT-PCR analysis, ELISA, and microcolorimetry. (3) Results: We found that DBD treatment reduced body weight loss, abnormal organ indices, abnormal blood cell counts, pathological damage to breast tissue, and the upregulation of the expression of inflammatory factor in mice caused by E. coli infection. We also found that DBD increased the expression of antioxidants and antioxidant genes and decreased the expression of oxidation products and oxidation-related genes in breast tissue. The therapeutic effect of DBD on inflammation and oxidative stress (OS) in mice occurred through the regulation of the TLR4/NF-κB and Nrf2/HO-1 signaling pathways. (4) Conclusions: DBD imparted its anti-inflammatory and antioxidant effects by inhibiting the TLR4/NF-κB signaling pathway and activating the antioxidant Nrf2/HO-1 signaling pathway